The Effect of Relationship Marketing on Customer Loyalty: The Case of Cooperative Bank of Oromia in Nekemte Town - Gudata Abara Chali (Jurnal Genesis Indonesia, 2026)
This study investigates the impact of relationship marketing—specifically Customer Relationship Management (CRM) practices—on customer loyalty at the Cooperative Bank of Oromia (CBO) in Nekemte town. Despite the rapid growth of the Ethiopian banking sector, competition for customer retention remains intense. Utilizing a descriptive and explanatory research design, the study collected primary data from 180 respondents using structured Likert-scale questionnaires. Data analysis was performed employing descriptive statistics, Pearson correlation, and multiple regression analysis. The findings reveal significant positive correlations between all six studied dimensions—Key Customer Focus, Interaction Management, CRM Organization, Knowledge Management, Technology-based CRM, and IT Integration—with customer loyalty. Regression results (R2=0.755) indicate that CRM practices explain 75.5% of the variance in customer loyalty. Notably, Technology (β=0.337) and ICT Integration (β=0.320) emerged as the most potent predictors. The study concludes that while CBO performs moderately in relationship marketing, a technology-driven, customer-centric approach is essential for long-term loyalty. Recommendations include upgrading digital banking infrastructures and enhancing personalized communication frameworks.